Classification of the Orthogonal Separable Webs for the Hamilton-Jacobi and Klein-Gordon Equations on 3-Dimensional Minkowski Space - Valero, Carlos; McLenaghan, Raymond G. (Symmetry, Integrability and Geometry: Methods and Applications, 2022)
We review a new theory of orthogonal separation of variables on pseudo-Riemannian spaces of constant zero curvature via concircular tensors and warped products. We then apply this theory to three-dimensional Minkowski space, obtaining an invariant classification of the forty-five orthogonal separable webs modulo the action of the isometry group. The eighty-eight inequivalent coordinate charts adapted to the webs are also determined and listed. We find a number of separable webs that do not appear in previous works in the literature. Further, the method used seems to be more efficient and concise than those employed in earlier works.